Pertanggungjawaban Notaris terhadap Perjanjian Kerja Sama dengan Bank Berdasarkan Undang-Undang Republik Indonesia Nomor 2 Tahun 2014 tentang Perubahan Atas Undang-Undang Nomor 30 Tahun 2004 tentang Jabatan Notaris - Firma Hot Tua Natalia Panjaitan (CV Rewang Rencang, 2025)
Cooperation agreement between the bank and the notary arose as the existence of a notary was very necessary in making deeds in the credit sector. This study examines the legal position of a notary in partner cooperation with a bank and the notary's responsibility for credit agreement deeds. With a Normative Juridical approach, the study shows, any violation committed by a Notary will be subject to sanctions in accordance with the Notary Law and the Notary Code of Ethics. The notary's responsibility towards his profession adheres to the principle of responsibility based on error, so that the Notary must be responsible if there is a mistake he makes. The notary also has the responsibility to be present when the bank credit agreement takes place and to determine the validity of the authentic deed he has made.